Effect of isovalent ion substitution on electrical and dielectric properties of LaCrO3 - Kumar P.; Singh R.K.; Sinha A.S.K.; Singh P. (My University, 2025)
In the present investigation, the effect of isovalent doping on the electrical and the dielectric properties of the system, La 1-xGdxCrO3 was studied. A few compositions of Gd doped lanthanum chromite, La1-xGdxCrO3 (x = 0.00, 0.01, 0.05, 0.10 0.15 and 0.20) were synthesised via auto-combustion route. The XRD patterns of all the compositions showed single phase formation having crystal structure similar to that of undoped LaCrO3. The Rietveld refinement of the XRD data of all the compositions indicated orthorhombic structure with space group Pnma at room temperature. The SEM micrographs revealed spherical, oval and irregular morphologies of all compositions having low porosity. The FTIR spectra of the investigated compositions showed various structural modes of vibrations. Real part of electrical conductivity exhibited frequency independent behaviour in the frequency range 20 Hz-1 MHz and in the temperature range 40-400°C. The DC conductivity of the system was found to show Arrhenius behaviour up to 300°C. The DC conductivity increased with x up to x = 0.01, the trend was reversed in the range 0.01 ≤ x ≤ 0.10 and thereafter it again increased with x up to x = 0.20. The temperature and composition dependent conduction mechanism was explained in terms of defects created due to change of concentration of dopant ion and the size difference between the host and dopant ions. The XPS analysis showed that the concentration of Cr6+ sites increased with the increase in Gd concentration, supporting the proposed conduction mechanism. The orientational and the space charge polarisation processes have been attributed to the total dielectric behaviour of the system in the measured frequency and temperature ranges. © 2013 Elsevier B.V. All rights reserved.